Maria Hellebergs 'Fremmede naboer' i den danske Polen-diskurs - Schab, Sylwia (Folia Scandinavica Posnaniensia, 2009)
The aim of the article is to place Maria Helleberg’s book Fremmede naboer (1992) in a broader cultural and literary context and to define its position in the Danish discourse on Poland. The author of the article points out some elements used for creating an image of Poland and confronts the image with the canonical representation of Poland from Georg Brandes’ text Indtryk fra Polen (1888). The result of the comparison mentioned above shows a certain conservatism in the way Poland is presented in Danish literary discourse. The conclusion is supported with references to other texts dealing with Polish matters from the period from 1888 to 2002.